Synthesis and odour evaluation of alcohols bearing a cis‐1, 2‐dimethyl norbornane moiety. (20th November 2012) - Clinet, Adrien; Chaignaud, Mathilde; Clinet, Jean‐Claude; Dunach, Elisabet
ABSTRACT The multi‐gram synthesis of a large series of differently substituted alcohols bearing a common cis‐1, 2‐dimethyl norbornane structure is described. Olfactive evaluation of the compound series is presented and reveals woody aspects as the predominant notes for most of the alcohols. Copyright © 2012 John Wiley & Sons, Ltd.